Cascade (Dithio)carbonate Ring Opening Reactions for Self‐Blowing Polyhydroxythiourethane Foams - Coste, Guilhem; Negrell, Claire; Caillol, Sylvain (Macromolecular rapid communications., 2022)
Polyurethane (PU) foams are very common materials that have found many applications over the years. Their use is constantly improving due to their unique physical properties and easy blowing which does not require the addition of a blowing agent. Greener routes have been explored in the recent years to replace isocyanates. One of the most promising routes is leading to polyhydroxyurethanes (PHU). However, with PHUs, external blowing agent are usually required to obtain a foam. Thus, the work focuses on PHU foam synthesis using in situ reaction to produce NIPU foam. Hence, the aminolysis of thiocyclic carbonate triggers Pearson reaction between released thiols and cyclic carbonates which serves as a chemical blowing agent. Non‐isocyanate polyurethane foams are synthesized by cascade aminolysis reaction of thio‐ and regular five membered cyclic carbonates. This cascade reaction allows the release of CO2 as sustainable blowing agent.